Seismic safety evaluation of concrete dams : a nonlinear behavioral approach - Zhang, Chuhan, editor of compilation; Jin, Feng, 1966-, editor of compilation; Wang, Jinting, 1973-, editor of compilation; Xu, Yanjie, 1970-, editor of compilation (Amsterdam : Butterworth-Heinemann, an imprint of Elsevier, 2013)
Includes bibliographical references and index.